2019
DOI: 10.1038/s41598-019-45818-4
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signalling mediates miR-133a nuclear re-localization for the transcriptional control of Dnmt3b in cardiac cells

Abstract: MiR-133a is a muscle-enriched miRNA, which plays a key role for proper skeletal and cardiac muscle function via regulation of transduction cascades, including the Wnt signalling. MiR-133a modulates its targets via canonical mRNA repression, a process that has been largely demonstrated to occur within the cytoplasm. However, recent evidence has shown that miRNAs play additional roles in other sub-cellular compartments, such as nuclei. Here, we show that miR-133a translocates to the nucleus of cardiac cells foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…C-Score-Combined Annotation Dependent Depletion (CADD) score is a broadly applicable metric that objectively weights and integrates diverse information that integrates multiple functional annotations into one metric by contrasting variants that survived natural selection with simulated mutations. has not yet been demonstrated, it has been shown that inactivated canonical WNT signaling facilitated nuclear entry of miR-133a and complexed with AGO2 to suppress DnmT3b expression in mouse HL-1 cells 50 . Also, the presence of p.Y544C impaired LRP6 localization to plasma membrane for facilitating WNT signaling 42 .…”
Section: Discussionmentioning
confidence: 97%
“…C-Score-Combined Annotation Dependent Depletion (CADD) score is a broadly applicable metric that objectively weights and integrates diverse information that integrates multiple functional annotations into one metric by contrasting variants that survived natural selection with simulated mutations. has not yet been demonstrated, it has been shown that inactivated canonical WNT signaling facilitated nuclear entry of miR-133a and complexed with AGO2 to suppress DnmT3b expression in mouse HL-1 cells 50 . Also, the presence of p.Y544C impaired LRP6 localization to plasma membrane for facilitating WNT signaling 42 .…”
Section: Discussionmentioning
confidence: 97%
“…Increasing evidence shows that this is true. For instance, several miRNAs that are prominently localized in the nucleus have been associated with transcriptional regulation [144]. Many miRNA-binding sites in gene promoters in sense and antisense orientations have been predicted by in silico analyses [145].…”
Section: Mirna-mediated Transcriptional Regulationmentioning
confidence: 99%
“…Another example of miRNA-mediated DNA methylation is described for miR-133a. The promoter of Dnmt3b contains a miR-133a binding site in pluripotent stem cells [144]. The interaction of miR-133a with the promoter of Dnmt3b recruits DNMT3B via direct binding to AGO2.…”
Section: Mirna-mediated Transcriptional Regulationmentioning
confidence: 99%
“…Function of tsRNAs binding to Argonaute (AGO) protein is similar to miRNAs [23]. Binding of nuclear miRNAs to promoters leads to activate [24][25][26] or silence [27][28][29] the transcription of target genes. Therefore, we speculate that tsRNAs are similar to miRNAs and play a regulatory role through targeting promoters.…”
Section: Construction Of Tsrna-promoter Interaction Networkmentioning
confidence: 99%